Dietary Lipid:Protein Ratio and n-3 Long-Chain Polyunsaturated Fatty Acids Alters the Gut Microbiome of Atlantic Salmon Under Hypoxic and Normoxic Conditions - Huyben, David; Roehe, Beeke K.; Bekaert, Michaël; Ruyter, Bente; Glencross, Brett (Frontiers in Microbiology, 2020)
Researchers have adjusted dietary lipid:protein ratios and n-3 long-chain polyunsaturated fatty acids (LC-PUFA) to optimise the growth performance of Atlantic salmon. However, dietary impacts on the gut microbiome is lacking, especially under varying environmental conditions. To examine this response, post-smolt salmon (184 ± 5 g) were fed diets with lipid:protein ratios considered low (180 : 570 g/kg) and high (460 : 230 g/kg) along with low and high levels of n-3 LC-PUFA (7 or 14 g/kg) while fish were reared under low and high levels of dissolved oxygen (6.7 or 8.0 mg/L). At day 0, 35 and 116, digesta in the distal intestine was collected and analysed for viable counts and 16S rRNA genes (V4 region) using Illumina MiSeq. The reduction in oxygen had negligible effects, except on viable plate counts of total bacteria and an initial effect on beta-diversity. In contrast, the high lipid diets had an increased alpha-diversity (e.g. Shannon and Chao-1) at day 0 and day 35 whereas high n-3 diets suppressed these indices at day 116. Generally, a reduction in alpha-diversity was observed over time and an interaction between lipid:protein ratio x n-3 was found. Between diets, beta-diversity and phyla abundance were similar as both Proteobacteria (44%) and Firmicutes (21%) dominated. However, at the genus level Aliivibrio, Streptococcus, Weissella and Lactobacillus, were associated with low lipid diets while the high lipid diets were associated with less abundant bacteria, e.g. Chromohalobacter. At day 116, the relative abundance of the Tenericutes phylum increased 10-fold (36%). Fish fed the high lipid diet with high n-3 had reduced alpha-diversity, lowest abundance of lactic acid bacteria and highest abundance of Mycoplasma, which may indicate a less healthy gut microbiome. PICRUSt analysis revealed that saturated and unsaturated fatty acid biosynthesis pathways were several folds higher in fish fed the high lipid diet, possibly to compensate for the lack of dietary n-3. In summary, our results show that the viable plate counts, alpha-diversity, beta-diversity and predictive function of gut bacteria in Atlantic salmon post-smolts are influenced by dietary lipid:protein ratio and n-3 LC-PUFA over several time points with little effect by dissolved oxygen.